RECOVERY OR NEW STRUGGLE? COMPETITIVE ADVANTAGE IN “THE CITY OF 1000 COFFEE SHOP” - Djunita Permata Indah; Ahmadi Ahmadi (SEAN Institute, 2023)
The coffee shop business is currently very popular with businesspeople, especially in Pontianak which has the nickname City of a Thousand Coffee Shops. This is driven by the cultural factors of the people of Pontianak who like to gather either with coworkers, or even families in modern and traditional coffee shops. This has caused the coffee shop business competition to be very high in Pontianak. Although during the covid-19 pandemic many coffee shops went out of business, in fact, new coffee shops are still proliferating. Therefore, this research focuses on the competitive advantages carried out by coffee shop business actors in order to survive during and after the pandemic. this research was conducted with a descriptive qualitative approach. the interview process is carried out until the data is saturated. The results showed a process of change in value chain management and operational processes in order to survive and improve hospitality to strengthen customer loyalty as a competitive advantage of coffee shops.